2009
DOI: 10.1002/aic.11876
|View full text |Cite
|
Sign up to set email alerts
|

Discrete element simulation of free flowing grains in a four‐bladed mixer

Abstract: Numerical simulations of granular flow in a cylindrical vessel agitated by a fourblade impeller were performed using the discrete element method. Velocity, density, and stress profiles within the mixer displayed a periodic behavior with a fluctuation frequency equal to that of the blade rotation. Blade orientation was found to affect flow patterns and mixing kinetics. For an obtuse blade pitch orientation, a threedimensional recirculation zone develops in-front of the blade due to formation of heaps where the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
69
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(73 citation statements)
references
References 36 publications
4
69
0
Order By: Relevance
“…1(c). Similar to the method suggested by Remy et al (2009) and Hare et al (2015 the measurement cell size is about 5-6 particle diameter. Based on the velocity gradient of particles, the strain rate in the measurement cells is given as:…”
Section: Snapshotsmentioning
confidence: 64%
See 1 more Smart Citation
“…1(c). Similar to the method suggested by Remy et al (2009) and Hare et al (2015 the measurement cell size is about 5-6 particle diameter. Based on the velocity gradient of particles, the strain rate in the measurement cells is given as:…”
Section: Snapshotsmentioning
confidence: 64%
“…Based on experiments and CFD simulations, Khalilitehrani et al (2013;2015) studied the rheology of dense granular flows in a disc impeller high shear granulator. Remy et al (2009Remy et al ( , 2011 carried out stress analyses of particle flow in a rotating blade mixer using DEM. They found that the normal and shear stresses were affected by the degree of polydispersity of particle size, and the shear stress was sensitive to the particle friction coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…The process uses Newton's laws of motion that gives 159 the relationship between the particle motion and forces acting on each particle. Translational and 160 rotational motions of a particle are defined as (Remy et al 2009 …”
mentioning
confidence: 99%
“…Fine tuning of the values of Poisson's ratio and Young's modulus is important because it decides the stiffness of the particles, which on the other hand controls the particle deformation or overlap upon contact. It is suggested that the particle overlap be controlled so that the model stays within the elastic limit [14].…”
Section: Introductionmentioning
confidence: 99%